An experimental study of modulus dispersion and attenuation in sandstones at seismic frequencies - Mikhaltsevitch, Vassili; Lebedev, Maxim; Gurevich, Boris (CSIRO, 2013)
A study of the low frequency dispersion and attenuation in sedimentary rocks is important for interpreting seismic data obtained during fluid extraction in producing fields or during injection of carbon dioxide for storage purposes. We present the results of the laboratory measurements of elastic and anelastic parameters of dry and distilled water/brine saturated sandstones with low (~7.8 and 9.6 mD) and high (~590 mD) permeability conducted at seismic (1-100 Hz) and teleseismic (0.1-1 Hz) frequencies. The experiments were performed with a laboratory apparatus utilizing stress-strain relationship which was developed to measure the complex Young’s moduli of rocks at seismic frequencies. The measurements carried out in saturated sandstones with low permeability at effective pressures from 2.5 to 23 MPa revealed prominent peaks of attenuation in the seismic and teleseismic bands. A significant dispersion of the Young’s moduli was also observed. The change in the salinity of the fluid from 0 to 45,000 ppm NaCl did not affect any of the measured parameters. The dispersion of the elastic moduli of the dry sandstones was within the accuracy of our measurements.